Solving Hashiwokakero Puzzle Game with Hashi Solving Techniques and Depth First Search - Reza Firsandaya Malik; Rusdi Efendi; Eriska Amrina Pratiwi (Institute of Advanced Engineering and Science, 2012)
Hashiwokakero is a logic puzzle game that sharpen the brain and very popular in Japan. This paper discusses about how to find a solution in the Hashi puzzle game using Hashi Solving techniques, such as: Just Enough Neighbor, One Unsolved neighbor, Few Neighbor, Leftovers and Isolation. Hashi Solving techniques are used to find and build bridges that can definitely be built across the island, while Depth First Search (DFS) will search and build bridges that have not been found by Hashi Solving techniques. The results shown that Hashi Solving Techniques and DFS able to solve every Hashi puzzle scenario.